ARID1A is a coactivator of STAT5 that contributes to CD8+ T cell dysfunction and anti-PD-1 resistance in gastric cancer - Fangqi Ma; Mingming Ren; Zhongqiu Li; Yujing Tang; Xiaoyu Sun; Yi Wang; Nida Cao; Xiaohong Zhu; Yan Xu; Rui Wang; Yumiao Shen; Ruohan Zhao; et al. (Pharmacological Research)
ARID1A deletion mutation contributes to improved treatment of several malignancies with immune checkpoint inhibitors (ICIs). However, its role in modulating of tumor immune microenvironment (TIME) of gastric cancer (GC) remains unclear. Here, we report an increase of CD8+ T cells infiltration in GC patients with ARID1A-mutation (MUT), which enhances sensitivity to ICIs. Kaplan-Meier survival analysis showed that ARID1A-mutation patients with gastrointestinal malignancies benefit from immunotherapy. Transcriptome analysis implicated that ARID1A regulates STAT5 downstream targets to inhibit T-cell mediated toxicity. Integrated dual luciferase assay and ChIP-qPCR analyses indicated that ARID1A coordinated with STAT5 to facilitate the transcription of the immunosuppressive factors TGF-β1 and NOX4. ARID1A recruited canonical BAF complex (cBAF) subunits, including SMARCB1 and SMARCD1, to sustain DNA accessibility. Downregulation of ARID1A reduced chromatin remodeling into configurations which make GC more sensitive to ICIs. In addition, targeting STAT5 effectively improved anti-PD-1 efficiency in ARID1A-wild type (WT) GC patients. Taken together, ARID1A is a coactivator of STAT5, function as a chromatin organizer in GC ICIs resistance, and targeting STAT5 is an effective strategy to improve the efficiency of ICIs in GC.